Efektivitas Gambir (Uncaria gambir Roxb.) sebagai Anti Hiperkolesterolemia dan Stabilisator Nilai Darah pada Mencit Putih (Mus musculus) Jantan - Desfita Frinanda; - Efrizal; Resti Rahayu (Universitas Andalas, 2014)
Research about the affectivity of gambier (Uncaria gambir Roxb.) as anti-hypercholesterolemic and stabilizer of blood value on the male white mice (Mus musculus) have been done from August to December 2013 in the Research Laboratory of Animal Physiology, Biology Department, Mathematics and Natural Sciences Faculty, Andalas University, Padang and Sejawat Clinical Laboratory, Padang. This study aimed to determine whether gambier could inhibit the increase in total cholesterol and stabilize blood value of white mice that were given with the leftover frying oil and to determine the best dose of gambier in inhibiting the increase in total cholesterol and stabilize blood value of white mice that were given with the leftover frying oil. This study used an experimental method completely randomized design (CRD) with five treatments and five replications. Treatment with giving the leftover frying oil and gambier dose of 50; 100; 150 and 200 mg/kg and control with giving the leftover frying oil without giving gambier. The result showed that the gambier could inhibit the increase in total cholesterol and stabilize blood of white mice that were given with the leftover frying oil and the best dose is 50 mg/kg body weight. Keywords : Uncaria gambir Roxb., anti hypercholesterolemic, Mus musculus